Early Disaster Recovery Strategy: The Missing Link in Post-Disaster Implementation in Indonesia - Medi Herlianto (Global Writing Academica Researching and Publishing, 2023)
Indonesia is a region that is prone to various types of disasters such as earthquakes, volcanic eruptions, tsunamis, rain fires, landslides and floods. As a country prone to natural disasters, Indonesia must have a disaster emergency response management with a clear concept of early recovery because Law No. 24 of 2007 and Government Regulation No. 21 of 2008 are not strictly regulated. This study aims to analyze post-disaster early recovery strategies which are the missing link in post-disaster implementation in Indonesia. This study uses a qualitative approach with the Miles & Huberman Interactive Analysis Model research method. 1992, where in this study the data analysis was carried out simultaneously with the data collection process and the flow of analysis followed an interactive analysis model. The results of the study show that the implementation of early disaster recovery in Indonesia does not yet have a clear legal umbrella and generally early recovery options are focused on recovering physical assets and ignoring traumatic recovery. The main activities of early recovery mainly only provide shelters for victims of damaged houses but other actions and activities towards humanitarian recovery have not been carried out optimally.